Improving the diagnosis and treatment of high‐risk localised or locally advanced prostate cancer. Issue 1 (January 2015) - Payne, Heather; Khoo, Vincent; Clarke, Noel; Beresford, Mark; Moore, Caroline; Aslett, Philippa; Bahl, Amit; Bhatt, Rupesh; Boustead, Greg; Brewster, Simon; Kirby, Roger
<x xml:space="preserve">Abstract</x> Radiologists, oncologists, urologists and clinical nurse specialists met to evaluate how patients with high‐risk localised or locally advanced prostate cancer might be better diagnosed and managed. In this first article, the authors look at ways in which the diagnosis of the disease could be improved and discuss how to optimise hormonal and radiotherapy. The second article in the series will evaluate surgical therapy.